Performance Analysis of Telecommunication System with Feedforward Control Mechanism - Navickas, Z.; Žvironienė, A.; Rindzevičius, R.; Tervydis, P. (Elektronika ir Elektrotechnika, 2010)
The proposed feedforward adaptive bitrate control method has advantages over feedback control scheme. Advantages of the method were demonstrated by means of simulation. Delayed feedback signal from long paths in IP network causes excessive queue growth and data packet loss. Adaptive local feedforward sender output bit rate control mechanism removes IP network delay impact to data packets transmission performance measures. The key component of the proposed feedforward sender output bit rate control mechanism is the way to compute the sender transmission bit rate matching with level of output buffer occupancy. Investigated bit rate control mechanism is based on generating feedback signal when the queue length in the output buffer exceeds the defined occupancy thresholds. The bit rate controller works according to a feedback signal, adaptively reducing or increasing sender output bit rate and keeps the system within an acceptable range of performance avoiding transmission link of congestion. Simulation model of proposed feedforward bit rate control mechanism based on Moore and Mealy automata is simple and universe. We carried out simulations to verify our proposed feedforward bit rate control mechanism and evaluate an effectiveness of our solution.